2015
DOI: 10.1016/s0924-9338(15)30181-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Predictors of Health Service Utilisation by Adults with Mental Disorders in the UK

Abstract: Objectives: To identify variables that predict health service utilisation (HSU) by adults with mental disorders in the UK, and to determine the evidence level for these predictors.Design: A narrative synthesis of peer-reviewed studies published after the year 2000. The search was conducted using four databases (ie, PsycINFO, CINAHL Plus with full text, MEDLINE and EMBASE) and completed on 25 March 2014. Setting:The majority of included studies were set in health services across primary, secondary, specialist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 12 publications
3
23
1
Order By: Relevance
“…Globally, the overall treatment gap for mental disorders exceeds 50%, rising up to 90% in low and middle income countries [5]. Causes for the treatment gap are multi-faceted, and include affected individuals, clinicians and societal factors [6, 7]. Awareness of mental health symptoms and relating them to a potential mental health problem has been shown to be an important predictor of perceived need and help-seeking intentions in persons with untreated mental disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the overall treatment gap for mental disorders exceeds 50%, rising up to 90% in low and middle income countries [5]. Causes for the treatment gap are multi-faceted, and include affected individuals, clinicians and societal factors [6, 7]. Awareness of mental health symptoms and relating them to a potential mental health problem has been shown to be an important predictor of perceived need and help-seeking intentions in persons with untreated mental disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the demand for health service utilisation related to methamphetamine is crucial for planning treatment programs and responding to additional demands on the health care system for both emergency and long term health care . Most research into health service use related to illicit drug use has focused on opioid use, injecting drug use and substance use generally .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research showed age, gender, ethnic, employment, and socio-economic differences in health and social care utilisation (Twomey et al 2015;Berthoud 2011). To control for the confounding effects of these variables on health and social care utilisation we included age (16-44 versus 45-64), gender, work status (not working/working), and ethnicity (white versus non-white) into the logistic regression model.…”
Section: Confounding Variablesmentioning
confidence: 99%